Democrazia partecipativa e organizzazioni politiche. I cantieri di Rita Borsellino (Democracy and Political Organizations. Rita Borsellino’s Cantieri) - Rossana Sampugnaro (Coordinamento SIBA, 2011)
This article is available on the website of the old publisher Franco Angeli ( http://www.francoangeli.it/riviste/sommario.asp?IDRivista=152 )